Antibiotic-Loaded Nano Drug Delivery Systems for the Treatment of Respiratory Tract Infections - Sukumaran, Dr. Sathesh Kumar (Asian Journal of Pharmaceutics (AJP), 2022)
Many antibiotics being currently used for the treatment of various infections face the problems such as short half-life, systemic toxicity, and increased susceptibility to bacterial resistance. Although, most antibiotic classes are administered systemically through oral or intravenous routes, a more efficient delivery system is needed for enhancement of the efficacy against the microorganisms and prevents the development of drug resistance. The exposure of subtherapeutic concentration of the antibiotics is considered as one among the major reason for the development of antibiotic drug resistance by the microorganisms. Incorporation of antibiotic drug-loaded nanoparticles for the treatment of respiratory tract infection shows a promising strategy to avoid rapid clearance from the lung and achieve sustained drug release. Many such reports are available, which scientifically exhibit the potential ability to achieve enhanced therapeutics response of antibiotics, when incorporated in an optimized nano-drug delivery system. This review discusses the approaches to be carried out for antibiotic loaded in nanodrug for enhancing the efficacy of antibiotics.